(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Astuti A, Nayasilana IN, Sugiyarto, Budiharjo A. 2022. Community structure of dragonflies (Odonata) in Gunung Bromo’s Forest Area with Special Purpose (FASP), Karanganyar, Central Java, Indonesia. Biodiversitas 23: 2493-2501. Dragonflies are one component of biodiversity in Indonesia, which function both as predators and bioindicators of water quality. Dragonfly habitat is widespread ranging from highland forest areas, lowland forests, reservoirs, lakes, rivers, swamps, and rice fields to settlements. One location that becomes dragonfly habitat is in the Gunung Bromo’s Forest Area with Special Purpose (FASP), Karanganyar, Central Java, Indonesia. This study aims to determine the community structure and habitat preferences of dragonflies in Gunung Bromo’s FASP. Data resulting from this study is expected used as a database for Gunung Bromo’s FASP managing. The study was conducted along the Bamban river which is located in the Gunung Bromo’s FASP area, in June-July 2019. Dragonflies were collected in 14 observation stations. At each observation, station transects were 100 m in length and 10 m in width. Data collection included the dragonflies species, the individual numbers, and environmental factors both abiotic and biotic factors. Data analysis included the diversity, evenness, dominance and similarity of dragonfly species. Principal Component Analysis (PCA) was applied to determine the dragonfly abundance pattern and Canonical Correspondence Analysis (CCA) was applied to determine the relationship between dragonflies and their environmental factors. The results showed there were 23 species of dragonflies in the Gunung Bromo’s FASP with a diversity index of 1.96. PCA results indicate the abundance of dragonflies is not much different in each species. Meanwhile, CCA results show almost of the dragonflies in the Gunung Bromo’s FASP are influenced by abiotic and biotic factors, except on Orthetrum sabina and Copera marginipes. They are assumed have unspecific habitat preferences.